Heterogenous Epoxidation of Isobutene Selectively Enabled by MoSe2 in Hexafluoroisopropanol (HFIP) - Xiaodao Liang; Chenghao Zhang; Yaorong He; Yanxiong Fang; Hongyu Chen; Hongbing Ji; Yan Yang (Molecules)
Herein, a high selective epoxidation of isobutene was achieved by heterogeneously dispersed MoSe2 with tert-butyl hydroperoxide (TBHP), which further showed versatile substrate scopes and well-retained activity among recycling tests. A rational mechanism is proposed based on extensive control experiments and electron paramagnetic resonance spectroscopy, surprisingly unveiling the metal–oxo and radical mediated pathways dramatically accelerated by hydrogen bonds of hexafluoroisopropanol (HFIP).